THE BOUNDEDNESS OF TOEPLITZ-TYPE OPERATORS ON VANISHING-MORREY SPACES - Cao, Xiaoniu; Chen, Dongxiang (Analysis in theory & applications, 2011)
In this note, we prove that the Toeplitz-type Operator b a generated by the generalized fractional integral, Calderon-Zygmund operator and VMO funtion is bounded from L^p,λ（R^n） to L^q,μ（R^n） . We also show that under some conditions Ob af ∈ VL^q,μ（BR） , the vanishing-Morrey space.